APLIKASI KLENTENG KOTA PEKANBARU BERBASIS WEBGIS - Ricandra Darwin; Rangga Rahmadian Yuliendi (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
There are more and more temples located in Pekanbaru City. Many people do not know the location of the temple and the activities they carry out related to stocks and minutes. Information received by the people tends to be slow or does not reach the people in need. This study aims to build a WebGIS-based pagoda application that provides information regarding the location and activities of the temple. The research method used is the System Development Life Cycle (SDLC) method. The system development refers to the CodeIgniter framework, then LeafletJS to display maps on the system, and Simple Mail Transfer Protocol (SMTP) to send a reply message to the pagoda via email. It is hoped that this application can make it easier for people to perform religious services where they want.